Prevalence of the most common external manifestations and comorbidities in men with decompensated alcoholic liver cirrhosis - Bokan, Goran; Mavija, Zoran; Kovačević, Marija; Bokonjić, Dejan; Prodanović, Verica (Vojnosanitetski pregled, 2025)
Background/Aim. External manifestations and comorbidities represent important clinical aspects of decompensated alcoholic liver cirrhosis (ALC), providing insight into disease severity and systemic involvement. The aim of the study was to examine the prevalence of external signs and comorbidities in male patients with decompensated ALC. Methods. A prospective, comparative, descriptive, and analytical study was conducted at the Clinic for Internal Medicine, University Clinical Center of the Republic of Srpska, in Banja Luka, Bosnia and Herzegovina. The study included 123 male patients diagnosed with decompensated ALC. All necessary diagnostic evaluations, including laboratory, microbiological, serological, radiological, and endoscopic assessments, were performed during their first hospitalization. Results. The mean age of the patients was 59.09 ± 9.32 years. The most common external manifestations were jaundice (79.67%), spider nevi (54.47%), palmar erythema (36.58%), and gynecomastia (18.69%). The most frequent comorbidities were diabetes mellitus (19.51%), congestive heart failure (17.88%), and chronic kidney disease (11.38%). A significant correlation was found between disease severity and the presence of external signs, with jaundice being the most prevalent. Conclusion. External manifestations and comorbidities are frequent in male patients with ALC, reflecting the systemic impact of the disease. Recognizing these clinical markers can aid in early diagnosis, risk stratification, and tailored therapeutic strategies.
Keywords: comorbidity; early diagnosis; liver cirrhosis, alcoholic; men